Optimalisasi Perkembangan Kognitif Anak Usia Dini melalui Bimbingan Penggunaan Game Edukasi Digital di TK Barunawati Ampenan - Putri, Dinda Riris Nurviana; Gunawan, Gunawan; Astini, Baik Nilawati (Indonesian Publication Center, 2023)
Cognitive development in early childhood is a crucial foundation for future learning success. In the digital era, following the challenges of the pandemic, the use of digital educational media has become highly relevant, yet it requires proper guidance for optimal results. This community service activity aimed to optimize the cognitive development of children aged 5-6 years at TK Barunawati Ampenan through guided use of digital educational games, specifically